Identification of ryuvidine as a KDM5A inhibitor - Mitsui, Eishin (Sci Rep, 2019)
KDM5 family members (A, B, C and D) that demethylate H3K4me3 have been shown to be involved in human cancers. Here we performed screening for KDM5A inhibitors from chemical libraries using the AlphaScreen method and identified a battery of screening hits that inhibited recombinant KDM5A. These compounds were further subjected to cell-based screening using a reporter gene that responded to KDM5A inhibition and 6 compounds were obtained as candidate inhibitors. When further confirmation of their inhibition activity on cellular KDM5A was made by immunostaining H3K4me3 in KDM5A-overexpressing cells, ryuvidine clearly repressed H3K4me3 demethylation. Ryuvidine prevented generation of gefitinib-tolerant human small-cell lung cancer PC9 cells and also inhibited the growth of the drug-tolerant cells at concentrations that did not affect the growth of parental PC9 cells. Ryuvidine inhibited not only KDM5A but also recombinant KDM5B and C; KDM5B was the most sensitive to the inhibitor. These results warrant that ryuvidine may serve as a lead compound for KDM5 targeted therapeutics.